Carbon stocks in coffee (C. arabica L.) agroforestry systems in the face of climate change: México case - Ruíz-García, Patricia (2022)
Introduction. Climate change can alter carbon (C) stocks stored in coffee agroforestry systems. Objective. To simulate C stocks in the aboveground biomass (ABOS) and soil (COS) at a fifty-years projection under the baseline and climate change scenarios in agroforestry systems with coffee, using the CO2Fix model. Materials and methods. In 2020, the baseline total C (ABOC + COS) was established in twenty-five organic coffee plots of the Catuai Amarillo S. de SS Society, Chcaman, Veracruz, Mexico. The plots were classified into three agroforestry designs: D1 (shade trees -coffee on slopes), D2 (shade trees -coffee-banana on slopes), and D3 (shade trees -coffee-banana in the valley). The CO2Fix model was used to simulate the total C stocks at a fifty-years projection under the baseline and climate change scenarios in the three agroforestry designs with coffee. Results. The total C in the baseline was 124.59, 107.43, and 102.320 t ha-1 for D1, D2, and D3, respectively. There were decreases between 0,77 and 8,75 t ha-1 in the low total C stocks under climate change scenarios in the three agroforestry designs evaluated. There were no statistically significant differences between agroforestry designs in the baseline and under climate change scenarios. Although variations were found, total C stocks were maintained over time. The tree cohort was the main storage source of total C storage. Conclusion. It was possible to simulate, in a fifty-year projection, the carbon stocks in aboveground biomass and soil in the baseline, under different climate change scenarios, using the CO2Fix model, in agroforestry systems with coffee from the Catuai Amarillo S. de S.S. Society.